Challenges in delivering bad news in a multi-ethnic intensive care unit: An ethnographic study. Issue 12 (December 2019) - Van Keer, Rose-Lima; Deschepper, Reginald; Huyghens, Luc; Bilsen, Johan
Highlights: The communication of bad news was primarily dominated by physicians. Patients' and relatives' input and other professionals' involvement was limited. Many difficulties occurred e.g . regarding the choice of conversation partner(s). Staff mainly tried to deal with problems themselves on the spot (quickly-ad hoc). Abstract: Objective: During critical care, physicians are frequently confronted with bad-news communication because of patients' frail conditions. Delivering bad news is not easy, certainly not when patients from ethnic minority groups are involved. In this study we investigate the delivery of bad news in a multi-ethnic critical care context. Methods: Ethnographic fieldwork in one intensive care unit of a multi-ethnic urban hospital in Belgium. Data were collected through negotiated interactive observation, in-depth interviews and from reading patients' medical records. Data were thematically analysed. Results: Bad-news communication was primarily dominated by physicians. Patients' and relatives' input and other professionals' involvement in the communication was limited. Staff encountered ethno-cultural related difficulties, firstly, in choosing suitable conversation partner(s); secondly, in choosing the place of conversations and thirdly, in the information exchange. Staff usually tried to address these problems themselves on the spot in a quick, pragmatic way. Sometimes their approaches seemed to be more emotion-driven than well thought-out. Conclusion: Delivering bad news in a multi-ethnic intensive care unit has a number of specific difficulties. These can have negative consequences for parties involved. Practice implications: The challenges of an adequate delivery of bad news need a team-approach and a well thought-out protocol.